Critical roles of regulatory B and T cells in helminth parasite-induced protection against allergic airway inflammation. (26th August 2019) - Gao, X; Ren, X; Wang, Q; Yang, Z; Li, Y; Su, Z; Li, J
Summary: The prevalence of allergic asthma and incidences of helminth infections in humans are inversely correlated. Although experimental studies have established the causal relation between parasite infection and allergic asthma, the mechanism of the parasite-associated immunomodulation is not fully elucidated. Using a murine model of asthma and nematode parasite Heligmosomoides polygyrus, we investigated the roles of regulatory B cells (Breg ) and T cells (Treg ) in mediation of the protection against allergic asthma by parasite. H. polygyrus infection significantly suppressed ovalbumin (OVA)-induced allergic airway inflammation (AAI) evidenced by alleviated lung histopathology and reduced numbers of bronchoalveolar inflammatory cell infiltration, and induced significant responses of interleukin (IL)-10 + Breg, IL-10 + Treg and forkhead box protein 3 (FoxP3) + Treg in mesenteric lymph node and spleen of the mice. Adoptive transfer of IL-10 + Breg and IL-10 + Treg cell prevented the lung immunopathology in AAI mice. Depletion of FoxP3 + Treg cells in FoxP3-diphtheria toxin (DT) receptor transgenic mice by diphtheria toxin (DT) treatment exacerbated airway inflammation in parasite-free AAI mice and partially abrogated the parasite-induced protection against AAI. IL-10 + Breg cells were able to promote IL-10 + Treg expansion and maintain FoxP3 + Treg cell population. These two types of Tregs failed to induce CD19 + B cells to transform into IL-10 + Breg cells. These results demonstrate that Breg, IL-10 + Treg and FoxP3 + Treg cells contribute in A discrepant manner to the protection against allergic airway immunopathology by parasiteS. Breg cell might be a key upstream regulatory cell that induces IL-10 + Treg response and supports FoxP3 + Treg cell population which, in turn, mediate the parasite-imposed immunosuppression of allergic airway inflammation. These results provide insight into the immunological relationship between parasite infection and allergic asthma. Graphical Abstract: